Energetics demands and physiological responses to boxing match and subsequent recovery - Nassib, S.; Hammoudi-Nassib, S.; Chtara, M.; Mkaouer, B.; Maaouia, G.; Bezrati-Benayed, I.; Chamari K. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Determining the physiological profile of athletes in boxing match is important for defining aspects of physical performance that are important to competitive performance. Therefore, examination of the energy pathway of high-level boxers` athletes can be very helpful for optimizing training and then improving boxing physical fitness and performance. The aim of the present study was to assess the physiological and cardiovascular responses during boxing matches and subsequent recovery. METHODS: Fifteen male international level boxers (mean age 19.56±3.6 years; mean body mass 72.46±11.86 kg; mean height 176.50±7.22 cm) participated in this study. Blood samples were drawn from the antecubital vein before and after the boxing matches (T1: pre-match rest measure around 11:00 a.m., T2: measure at 3 minutes of post-match recovery; T3: measure at 60 minutes of recovery; T4: measure at 24 hours post-match — the match started around 11:30 a.m.). An analysis of glucose, triglycerides, lactate, cholesterol, creatinine, uric-acid, high density lipoprotein, and low density lipoprotein concentrations was performed for each sample. Participants did perform a maximal incremental test to measure maximal heart rate (HRmax). Heart rate responses to the matches were measured and expressed in percentage of HRmax. RESULTS: The average HR recorded during the match corresponded to 93±3.26% of HRmax. The levels of glucose, lactate, and cholesterol increased significantly from T1 to T2. Likewise, creatinine levels increased significantly from T1 to T2 and T3. However, the cholesterol level decreased significantly at T3 in comparison with T1. Moreover, 24-hour post-match creatinine levels were significantly lower and triglyceride levels were significantly higher compared with T1. CONCLUSIONS: The main results of this study revealed that the boxing matches stress the lipid metabolism system during boxing and post-match (for at least 24 hours) even if it is widely recognized boxing being mainly composed of repeated short-duration anaerobic efforts.